Heat Recovery Potential and Hydrochemistry of Mine Water Discharges From Scotland’s Coalfields - David B. Walls; David Banks; Tatyana Peshkur; Adrian J. Boyce; Neil M. Burnside (Earth Science, Systems and Society)
Prospective and operational mine water geothermal projects worldwide have faced challenges created by mine water chemistry (e.g., iron scaling, corrosion) and high expenditure costs (e.g., drilling or pumping costs) among others. Gravity fed or actively pumped drainages can be cheaper sources of low-carbon mine water heating when coupled with adequately sized heat exchanger and heat pump hardware. They also provide valuable chemical data to indicate mine water quality of associated coalfields. Field collection of temperature and flow rate data from mine water discharges across the Midland Valley of Scotland, combined with existing data for Coal Authority treatment schemes suggest that mine water heat pumps could provide a total of up to 48 MW of heat energy. Chemical characterisation of mine waters across the research area has created a valuable hydrochemical database for project stakeholders investigating mine water geothermal systems using boreholes or mine water discharges for heating or cooling purposes. Hydrochemical analytical assessment of untreated gravity discharges found that most are circumneutral, non-saline waters with an interquartile range for total iron of 2.0–11.6 mg/L. Stable isotope analysis indicates that the discharges are dominated by recent meteoric waters, but the origin of sulphate in mine waters is not as simple as coal pyrite oxidation, rather a more complex, mixed origin. Untreated gravity discharges contribute 595 kg/day of iron to Scottish watercourses; thus, it is recommended that when treatment schemes for mine water discharges are constructed, they are co-designed with mine water geothermal heat networks.